Abnormal distribution of c-myc oncogene product in familial adenomatous polyposis. Issue 11 (November 1987) - Sundaresan, V; Forgacs, I C; Wight, D G; Wilson, B; Evan, G I; Watson, J V
Abstract : Monoclonal antibodies raised by synthetic peptide immunisation were used to determine the distribution of the protein product of the c-myc gene by immunocytochemical staining of archival wax embedded material from patients with familial adenomatous polyposis. Polyps from 18 cases of familial adenomatous polyposis, 10 of whom had developed malignant change, and 30 normal control colonic biopsy specimens were examined. A consistent staining pattern was observed in normal mucosa; nuclear staining in the basal proliferative zone; mixed nuclear and cytoplasmic staining in the maturation zone; and cytoplasmic localisation in the surface mature zone. In contrast, the polyps and carcinomata showed a mixed pattern of cytoplasmic and nuclear localisation in the basal proliferative zone with nuclear persistence throughout the crypts to the surface mature zone. This abnormal distribution of the c-myc oncogene product may have a role in the evolution of polyps and their subsequent malignant transformation into familial adenomatous polyposis.